3D kinematics of a thick salt layer during gravity-driven deformation. (December 2019) - Kirkham, Chris; Cartwright, Joe; Bertoni, Claudia; Rodriguez, Karyna; Hodgson, Neil
Abstract: We present the results of an interpretation of 2D and 3D seismic from offshore Lebanon in which we identify a suite of 5 linearly distributed trails of fluid escape pipes with pockmarks at their upper terminus. These features transect the thick Messinian evaporites and root within prominent NE-SW oriented pre-salt folds. The pipe trails are oriented orthogonal to the strike of the pre-salt folds, with a synchronous initial expulsion episode in each trail dated at 1.7 Ma (±0.3 Ma), approximately coeval with the onset of salt-detached growth faulting along the basin margin. Each expulsion episode has been systematically offset to the NW away from the pre-salt fold by the flow of the salt, resulting in deformation of the fluid escape pipes in the salt. The orientation of the pipe trails thus provides a direct kinematic indicator for the flow direction of the salt layer during early stages of gravity-driven deformation of the salt and overburden, concomitant with basin margin uplift and tilting. The unidirectional NW oriented flow is recorded over a region of some 50 km width within the translational domain of the salt tectonic deformation. Synchronicity in the onset of fluid expulsion from overpressured reservoirs within the pre-salt succession evidenced by these pipe trails and growth fault development at the basin margins implies that the pipe trails record the kinematics of the deforming salt layer throughout its post-Messinian phase of deformation. The deformed pipe trails demonstrate a Couette flow regime for the salt layer and document subtle changes in cumulative strain and velocity (2–4 mm/yr; ±0.3 mm/yr) over distances of a few km. It is proposed that this novel method of using fluid flow features as natural markers for the kinematics of deforming salt layers could be utilized in other parts of Eastern Mediterranean, as well as other salt basins on Earth. Highlights: Calibration of the 3D kinematics of a salt sheet deforming under gravity. Multi episode fluid expulsion through 'sealing' salt. Fluid escape pipes as natural strain markers through a salt sheet. Pipe trails reveal unidirectional flow, Couette flow regime and salt flow velocity. Lateral variation in salt flow velocity due to converging streamlines in salt.